Quality and accuracy of electronic pre-anesthesia evaluation forms. (July 2018) - Almeshari, Meshari; Khalifa, Mohamed; El-Metwally, Ashraf; Househ, Mowafa; Alanazi, Abdullah
Highlights: Pre-anesthetic evaluation is extremely important in reducing morbidity and mortality through the review of the patient's medical history, targeted clinical studies, clinical examination, and providing referrals for medical consultations when appropriate. The study demonstrates that the electronic pre-anesthesia form has better data quality and meets the expectations of anesthetists. Electronic pre-anesthesia form markedly supports to reduce time-consuming tasks, captures more details and provides immediately available data for quality assurance activities. Abstract: Background and Objective: Paper-based forms have been widely used to document patient health information for anesthesia; however, hospitals are now switching to electronic patient file documentation for anesthesia. The aim of this study is to compare the quality of paper-based and electronic pre-anesthesia assessment forms. Methods: The research conducted in this study was quasi-experimental using a pretest–posttest design without a control group. The study was conducted at King Abdulaziz Medical City, Riyadh (KAMC-RD) during November 2015. Paper-based forms were converted into electronic forms, and the paper-based pre-anesthesia forms were used during the first two weeks of the data collection period while electronic forms were completed in the last two weeks. The quality of each (electronic vs. paper) was evaluated with respect to missing items, errors, and unreadable items. The sample size included all 15 anesthetists working in the pre-anesthesia clinic at KAMC-RD. The anesthetists completed 25 pre-anesthesia forms daily during a five-day week schedule. A total of 500 patient forms were completed during the study (250 paper-based and 250 electronic forms). Anesthetists' satisfaction with the electronic pre-anesthesia form was also measured using a questionnaire. Results: The electronic form shows significantly higher quality in all assessment categories (missing items, errors, and unreadable items; X² (2, N = 500) = 171.64, p  < 0.001). The satisfaction survey found 81.65% of the anesthetists were satisfied with the electronic pre-anesthesia form for all questions. Conclusion: Our study demonstrates that the electronic pre-anesthesia form has better data quality, meets the expectations of anesthetists and aids to decrease missing key preoperative information. This type of approach is imperative for the safety of perioperative patients.